2021
DOI: 10.5194/hess-2021-261
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preprocessing approaches in machine learning-based groundwater potential mapping: an application to the Koulikoro and Bamako regions, Mali

Abstract: Abstract. Groundwater is crucial for domestic supplies in the Sahel, where the strategic importance of aquifers can only be expected to increase in the coming years due to climate change. Groundwater potential mapping is gaining recognition as a valuable tool to underpin water management practices in the region, and hence, to improve water access. This paper presents a machine learning method to map groundwater potential and illustrates it through an application to two regions of Mali. A set of explanatory var… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In some cases, authors found some vegetation related indices such as Normalized Difference Vegetation Index (NDVI) and Normalized Difference Water Index (NDWI) to be necessary for their groundwater level prediction studies (Gómez-Escalonilla, et al, 2022a;Gómez-Escalonilla, et al, 2022b). High NDVI values from natural vegetation may potentially suggest the likelihood of groundwater availability (Sahour et al, 2022) as well as the NDWI which can detect water content and the presence of water bodies or moisture in the landscape.…”
Section: Geological Variables and Their Effects On Groundwater Occurr...mentioning
confidence: 99%
See 3 more Smart Citations
“…In some cases, authors found some vegetation related indices such as Normalized Difference Vegetation Index (NDVI) and Normalized Difference Water Index (NDWI) to be necessary for their groundwater level prediction studies (Gómez-Escalonilla, et al, 2022a;Gómez-Escalonilla, et al, 2022b). High NDVI values from natural vegetation may potentially suggest the likelihood of groundwater availability (Sahour et al, 2022) as well as the NDWI which can detect water content and the presence of water bodies or moisture in the landscape.…”
Section: Geological Variables and Their Effects On Groundwater Occurr...mentioning
confidence: 99%
“…Land use and land cover integration is frequently employed in studies that map groundwater potential. This approach recognizes that land use changes, primarily driven by human activities, can significantly impact groundwater resources (Gómez-Escalonilla et al, 2022a).…”
Section: Geological Variables and Their Effects On Groundwater Occurr...mentioning
confidence: 99%
See 2 more Smart Citations
“…Because each model has its limitations, none was previously considered to be the ideal one for GWP modeling (Mallick et al, 2021;Gómez-Escalonilla et al, 2022). This is why researchers tried to integrate ensemble machine learning approaches, statistical techniques, and machine learning techniques in GWP modeling (Cai et (Islam et al, 2021a;Talukdar et al, 2021a;Talukdar et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%